THU0035 Understanding the GAP between Subjective Symptoms and Objective Illness Markers in Primary SjÖGren's Syndrome. (10th June 2014) - Robinson, L.; Hackett, K.; Bowman, S.; Griffiths, B.; Ng, W.; Gallagher, P.
Abstract : Background: There is an inconsistent relationship between subjective symptoms and objective markers of disease activity in individuals with Primary Sjögren's Syndrome (PSS). This presents a significant barrier to developing treatments if modifying disease markers does not translate into lower perceived symptoms. Little is known about the reasons for this discrepancy. Objectives: To identify subgroups of PSS patients that vary in the correspondence between subjective symptoms and objective levels of illness. Methods: The UK Primary Sjögren's Syndrome Registry (n=688) was used. Measures included subjective ocular and oral dryness, objective tear and saliva production, depression and anxiety (HADS), pain, fatigue and quality of life (EQ 5D TTO). Patients were divided into the top and bottom 30th percentiles on subjective and objective dryness and classed as "high" or "low" (middle scorers disregarded). Four groups were derived – Accurate Severe (high perceived dryness, low tear/saliva production), Accurate Mild (low perceived dryness, high tear/saliva production), Stoic (low perceived dryness, low tear/saliva production) and Sensitive (high perceived dryness, high tear/saliva production). The groups were compared on measures of mood, anxiety, pain, fatigue and quality of life. Results: Data from the classification based on ocular dryness are reported. There were: 55 Sensitive, 71 Accurate Severe, 85 Accurate Mild and 59 Stoic. On all measures, the Sensitive group rated themselves as having worse symptoms and poorer functioning, followed in order by the Accurate Severe group, the Accurate Mild group, and the Stoic group. Comparing the groups using ANOVA with follow-up comparisons indicated no statistically significant differences between the Sensitive and the Accurate Severe groups (all p>0.39), except for pain – the Sensitive group reported significantly higher pain than the Accurate Severe group (p=0.02). The Sensitive group rated themselves significantly worse on all measures compared to the Accurate Mild and Stoic groups (all p<0.001). The Stoic group rated themselves significantly better on all measures than the Sensitive and Accurate Severe groups (all p<0.04). The Stoic group rated themselves significantly less fatigued than the Accurate Mild group (p<0.03). Overall a very similar pattern was noted for oral dryness. Conclusions: Subgroups were identified based on the correspondence between subjective symptoms and objective illness markers. Patients whose perceived dryness was higher than would be anticipated from objective measurements reported the highest level of symptoms on all measures and the poorest quality of life. The opposite was the case for those whose subjective symptoms were lower than their objective illness markers would indicate. Although objective measures are subject to several confounds, nonetheless these findings suggest further investigation of these groups, exploring biological and psychological factors that may relate to symptom sensitisation, could be of significant value in elucidating our understanding of the path from symptom to distress and disability. This may ultimately guide intervention strategies. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2464